IMPLEMENTATION OF TAX INVOICE CRIME PREVENTION POLICY IN INDONESIA - Satria Fahmi, Helmi; Nurdin, Nurliah (DIA: Jurnal Administrasi Publik, 2025)
Fiscal policy plays an important role in economic growth and maintaining inflation stability. VAT is one of the tax innovations and has experienced tremendous development. Crimes against tax invoices include not depositing taxes that have been collected and issuing and/or using tax invoices that are not based on actual transactions, often called Fictitious/unauthorized Tax Invoice. This research is expected to explain the factors that influence the implementation of tax invoice crime prevention policies. This research uses a qualitative method. The data collection method is done by observation, in-depth interview, and FGD. There were 13 Tax Investigators, 2 Tax Practitioners, and 4 Academics as informants who were interviewed and involved in FGDs. The results of the research on the implementation of the tax invoice crime prevention policy concluded that an integrated tax invoice crime prevention policy strategy framework is needed starting from the stage of confirming PKP until the tax invoice is issued and reported on the VAT periodic tax return. In addition, accuracy of information, consistency in application and clarity of feedback are required. Continuous improvement of procedures and political support from policy makers are absolutely necessary. Further steps are needed to publish the policy framework of the Tax Invoice crime prevention strategy in Indonesia in a regulation issued by the Director General of Taxes which is expected to be implemented properly